Psychology, IUPsyS global resource - Overmier, J. Bruce; Overmier, Judith A., 1939-; International Union of Psychological Science; International Congress of Psychology (Hove, East Sussex, UK : published on behalf of the international Union of Psychological Science by Psychology Press Ltd., 2000)
An integrated set of searchable resources organized as separate information files and databases. Contains directories, bibliographies, surveys, historical records, and descriptive texts, including: Worldwide directory of psychology departments and research institutes, National survey and reports on status of psychology, Bibliography on psychology nationally and worldwide, Directory of international psychological organizations, International Congress of Psychology, Directory of child-family research centres in developing countries and Eastern Europe, Directory of health psychology in Latin America, International survey on ethics codes in psychology, and: International survey on cognitive science
Edition 2009
Title from opening screen
System requirements: IBM compatible PC; Windows 95 or higher
Interactive CD-Rom launched by: the International Union of Psychological Science
Included with some issues of: International journal of psychology
Keywords: Psychology -- Database; Psychology -- Directory; Psychology -- Resource Guides